Sleep and Quality of Life Improvements after Endoscopic Sinus Surgery in Patients with Chronic Rhinosinusitis - Alt, Jeremiah A. (2014)
BACKGROUND: Recent investigation has demonstrated that approximately 75% of patients with medically refractory chronic rhinosinusitis (CRS) report abnormal sleep quality, with strong correlation between worse sleep quality and more severe CRS disease severity. It remains unknown whether the treatment effect of endoscopic sinus surgery (ESS) for CRS results in appreciable sleep quality improvements. METHODS: Adult patients (aged ≥18 years) with a current diagnosis of recalcitrant chronic rhinosinusitis (CRS), who voluntarily elected ESS as the next treatment modality (n=301), were prospectively evaluated within four academic, tertiary care centers using treatment outcome instruments: the Rhinosinusitis Disability Index, the 22-item Sinonasal Outcome Test, the 2-item Patient Health Questionnaire, and the Pittsburgh Sleep Quality Index (PSQI) both before and after ESS. RESULTS: 72% of patients with CRS were found to have poor sleep (>5) at baseline with a mean global PSQI score of 9.4(4.6). Surgery improved overall mean global PSQI scores (2.2 points), and all 7 subdomain scores of the PSQI. Similarly, the odds of good sleep quality (PSQI ≤5) in patients treated with sinus surgery increased significantly (OR: 5.94, 95% CI: 3.06, 11.53; p<0.001). Stepwise multivariate linear regression found that ASA intolerance (β= −1.94(0.93); 95% CI: −3.77, −0.11; p=0.038), history of prior sinus surgery (β=1.10(0.54); 95% CI: 0.03, 2.16; p=0.044), and frontal sinusotomy (β= −1.03(0.62); 95% CI: −2.26, 0.20; p=0.099) were found to significantly associate with improvement in PSQI sleep scores. CONCLUSIONS: Among patients with CRS, reduced sleep quality, poor disease-specific quality of life, and greater disease severity were improved following ESS.